2010
DOI: 10.1097/brs.0b013e3181c7cf4b
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Root Sedimentation Sign

Abstract: A positive sedimentation sign exclusively and reliably occurs in patients with LSS, suggesting its usefulness in clinical practice. Future accuracy studies will address its sensitivity and specificity. If they confirm the sign's high specificity, a positive sedimentation sign can rule in LSS, and, with a high sensitivity, a negative sedimentation sign can rule out LSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 49 publications
4
53
3
1
Order By: Relevance
“…A3 in the morphological grade), the latter being measured above and/or below the level of maximal stenosis, at pedicle level. This was done in accordance with the recommendations of the original Barz et al paper as well as personal communication to us by the authors who state that ''at the level of the stenosis, nerve roots lie tightly packed in the dural sac and, therefore, cannot be identified and judged adequately'' [4].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A3 in the morphological grade), the latter being measured above and/or below the level of maximal stenosis, at pedicle level. This was done in accordance with the recommendations of the original Barz et al paper as well as personal communication to us by the authors who state that ''at the level of the stenosis, nerve roots lie tightly packed in the dural sac and, therefore, cannot be identified and judged adequately'' [4].…”
Section: Methodsmentioning
confidence: 99%
“…2 Nerve root sedimentation sign: comparison of MRI scans with a negative sedimentation sign (left) and a positive sedimentation sign (right) [4] Eur Spine J a positive predictive value 94 % and a negative predictive value of 45 %. The presence of a C or D morphological grade carried an OR of 14 between those two groups.…”
Section: Lss Vs Lbp Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Barz et al 23 introduced the sedimentation sign on magnetic resonance imaging (MRI) as a possible aid in decision making for LSS. Normally, in the supine position the lumbar nerve roots should settle to the posterior spinal canal due to gravity and the absence of constrictive force.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, in the supine position the lumbar nerve roots should settle to the posterior spinal canal due to gravity and the absence of constrictive force. A positive sedimentation sign, however, is evident when a patient lying supine has the absence of posterior nerve root settling 1,14,2324 . A previous study by Barz et al 23 demonstrated the ability of the sedimentation sign to discriminate between known cases of symptomatic central LSS and controls with non-specific low back pain (LBP).…”
Section: Introductionmentioning
confidence: 99%